SINTESIS DAN UJI AKTIVITAS ANTIBAKTERI SENYAWA TURUNAN AMOKSISILIN TERHADAP Escherichia coli - Hadi Barru Hakam Fajar Siddiq, Siti Nur Azizah, Amaliyah Nurul Hidayah, Dewi Riskha Nurmalasari, Mau (AKADEMI FARMASI JEMBER, 2019)
Amoxicillin derivate compounds from the reaction of amoxicillin with p-aminophenol are synthesized compounds by reacting amoxicillin and p-aminophenol. . Escherichia coli is a flora normal bacteria that can causing infectious diseases. This research aimed to determine the antibiotic activity of amoxicillin derivat compound (amoxicillin with p-aminophenol) on the growth of E. coli. This research was conducted using the disc diffusion method. amoxicillin derivat compound (amoxicillin with p-aminophenol) were characterized by organoleptic test, melting point determination, pH test determination, Rf value, and maximum wavelength. The results of the organoleptic test showed that amoxicillin derivates from amoxicillin and p-aminophenol reaction is crystal powder, dark brown and bit bitter. Melting point of amoxicillin derivates from amoxicillin and p-aminophenol reaction was 160ºC. pH test of amoxicillin derivates from amoxicillin and p-aminophenol reaction was 6,5. Rf value of amoxicillin derivates from amoxicillin and p-aminophenol reaction was 0,79. The results of UV wavelength scanning showed that amoxicillin derivates from amoxicillin and p-aminophenol reaction at 295 nm. Antibiotic activity showed by the clear zone form around the paper disk. The results showed that E. coli was resistant to pure amoxicillin. Amoxicillin derivat compound (amoxicillin with p-aminophenol) with concentrations of 100% and 12,5% have the largest inhibitory zones (6,33 mm) compared with concentrations of 50% and 25%, 5,33 and 6,00 mm respectively. Based on these results it can be concluded that derivat compound of amoxicillin (amoxicillin with p-aminophenol) has antibiotic activity against the growth of E. coli that has been resistant to pure amoxicillin.Keywords: Derivate compound of amoxicillin, Escherichia coli, antibiotic activity